Experimental installation of wireless power transfer system based on the series resonance technology - Sarab Al-Chlaihawi; Adnan Hasan Tawafan; Fatima Kadhem Abd (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this work, we aim to install a wireless power transfer (WPT) system experimentally. Series resonance technology was used to achieve zero-voltage switching (ZVS). We investigated the impact of the primary and secondary resonance frequencies (fp and fd), and inverter frequency switching (fch) on the efficiency (β) and maximum transfer power in a WPT system based on the inductive wireless power transfer (IWPT) technology. An ultrasonic device was utilized as a generator to excite the coil at the primary side. The experimental outcomes showed that there is an optimum unlike fp and fd can be got to match fch. It was found also that there is a trade-off between the power supplied to the load (PRL) and DC-DC efficiency (β). At an air-gap of 5 cm, the obtained results are recorded as follows; the peak recorded system β is 62% that was obtained at fp=19 kHz, fd=fch=24 kHz that is corresponding to 101.88W of PRL; whereas the highest PRL resulted i.e. 244W when fp=19 kHz, fd =24 kHz, fch=21 kHz at 61% of β; in such case, the maximum β* PRL multiplication was achieved i.e. 149. Moreover, the coils’ misalignment was studied. The outcomes showed that the lateral misalignment has worst effect on the PRL and β than the air-gap. The experimental results were validated with simulation ones.